2020
DOI: 10.1101/2020.05.11.088625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary intervention improves health metrics and life expectancy of the genetically obese DU6 (Titan) mouse

Abstract: Metabolic syndrome is widespread and negatively impacts healthy longevity but takes years to study in mammalian models, delaying translational applications. To address this, we characterized the unique polygenic "Titan" mouse (110 grams average) with a healthy lifespan of only 4 months that was generated by 45 years of breeding selection. Titan mice displayed increased plasma leptin, insulin, IL-6 and fasting triglycerides. Also, pancreatic fat cell accumulation and thymic medullary hyperplasia were detected i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 154 publications
(355 reference statements)
1
4
0
Order By: Relevance
“…Late dietary restriction in these mice demonstrated antiobesity effects including decrease in fat content and improvement of expression of genes involved in lipid synthesis. This supports the use of “Titan” mice as a model of metabolic disorders, systemic inflammation, and early aging [ 55 ].…”
Section: Animal Models In Metabolic Syndrome Researchsupporting
confidence: 68%
See 1 more Smart Citation
“…Late dietary restriction in these mice demonstrated antiobesity effects including decrease in fat content and improvement of expression of genes involved in lipid synthesis. This supports the use of “Titan” mice as a model of metabolic disorders, systemic inflammation, and early aging [ 55 ].…”
Section: Animal Models In Metabolic Syndrome Researchsupporting
confidence: 68%
“…Metabolic syndrome negatively affects healthy longevity but takes years to study in mammalian models, thereby delaying the development of translational applications [ 55 ]. Therefore, development of genetic mammalian models with shortened lifespan and fast progression to an obese phenotype has become a convenient approach to use for obesity studies.…”
Section: Animal Models In Metabolic Syndrome Researchmentioning
confidence: 99%
“…Furthermore, higher expression of hepatic PPAR- α , induced by intermittent fasting (20 h feeding +4 h fasting, 4 h feeding +20 h fasting and 24 h feeding +24 h fasting), decreased systemic inflammation by reducing the number of circulating monocytes in mice ( Jordan et al, 2019 ). A recent study in mice showed that even modest and relatively late dietary intervention ( ad libitum of 16.4% calorie reduced feed, starting at 12 weeks of age) in Titan obese mice is sufficient to reduce lipid content and improve life span ( Müller-Eigner et al, 2021 ).…”
Section: Therapeutic Interventions Targeting Lipids To Improve Health...mentioning
confidence: 99%
“…In line with the obese phenotype, DU6 candidate genes overlapping RDDs regulate energy metabolism and food intake ( Hcrt 94 ) and are linked to feed efficiency and body composition in other species ( Atp11 95 , Wdr27 96 ). On the other hand, DU6 mice also exhibit larger bones 59 and the analysis of SVs detected Smad5 , a modulator of bone formation 97 , to be partially overlapped by a heterozygous deletion and a heterozygous inversion. Candidate genes in the RDDs for DU6P conform with growth-related major quantitative trait loci found in sheep and are known to influence stature and body size in cattle, pigs and human ( Plag1 98,99 , Chchd7 98100 , Impad1 101 ).…”
Section: Resultsmentioning
confidence: 99%
“…1J). With the exception of the obese line DU6 59 , each one of the trait-selected mouse lines has developed an extreme phenotype without obvious detrimental effects on their general health, well-being and longevity.…”
Section: Phenotypic Impact Of Selectionmentioning
confidence: 99%